2021
DOI: 10.1007/s00401-021-02367-3
|View full text |Cite
|
Sign up to set email alerts
|

Altered ceramide metabolism is a feature in the extracellular vesicle-mediated spread of alpha-synuclein in Lewy body disorders

Abstract: Mutations in glucocerebrosidase (GBA) are the most prevalent genetic risk factor for Lewy body disorders (LBD)—collectively Parkinson’s disease, Parkinson’s disease dementia and dementia with Lewy bodies. Despite this genetic association, it remains unclear how GBA mutations increase susceptibility to develop LBD. We investigated relationships between LBD-specific glucocerebrosidase deficits, GBA-related pathways, and α-synuclein levels in brain tissue from LBD and controls, with and without GBA mutations. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 95 publications
0
43
2
Order By: Relevance
“…GCase is an enzyme that hydrolyzes glucosylceramide (GlcCer) and glucosylsphingosine (GlcSph) into glucose and ceramide or sphingosine, respectively [ 64 ]. CSF GCase activity has been shown to be significantly reduced in PD as well as in DLB compared to controls [ 65 , 66 , 67 , 68 , 69 , 70 ].…”
Section: Lysosomal Biomarkersmentioning
confidence: 99%
“…GCase is an enzyme that hydrolyzes glucosylceramide (GlcCer) and glucosylsphingosine (GlcSph) into glucose and ceramide or sphingosine, respectively [ 64 ]. CSF GCase activity has been shown to be significantly reduced in PD as well as in DLB compared to controls [ 65 , 66 , 67 , 68 , 69 , 70 ].…”
Section: Lysosomal Biomarkersmentioning
confidence: 99%
“…Sporadic PD patients also have altered levels of glucosylceramide and ceramide, the substrate and product of GCase enzyme activity (Mielke et al, 2013 ; Guedes et al, 2017 ), further supporting the observation that GBA enzymatic dysfunction is not a prerequisite for ceramide accumulation. EVs isolated from PD patient brain tissue were found to have increased levels of membranous ceramides that increased binding affinity for α-syn, leading to increased α-syn accumulation, aggregation, and propagation (Kurzawa-Akanbi et al, 2021 ). These studies suggest that reduced GCase activity and the resulting alterations in lipid metabolism are critical in the pathogenic process causing PD.…”
Section: Lipid Metabolism In Neurodegenerationmentioning
confidence: 99%
“…The reduction of ceramide, which is critical for ESCRT-independent exosome release, with inhibition of neutral sphingomyelinase 2 (nSMase2) reduced the spread of α-syn among co-cultured SH-SY5Y cells (Sackmann et al, 2019 ). A recent study of brain tissue and CSF of patients with PD or DLB with and without GBA mutations found that there was a significant increase in several ceramide species in brain tissue and EVs isolated from CSF from all disease patients compared to control, independent of GBA genotype (Kurzawa-Akanbi et al, 2021 ). Interestingly, proteomic analysis revealed the presence of α-syn, β-syn, gamma-syn, and tau in both disease and control EVs, with no significant difference in levels between either group.…”
Section: Lipid Alterations Influencing Exosomes and Progression Of Neurodegenerationmentioning
confidence: 99%
See 1 more Smart Citation
“…103 More recently, Morris and colleagues revealed that Lewy body disorders extracellular vesicles constitute a “pathological package” that is capable of inducing aggregation of wild‐type alpha‐synuclein. 104 …”
Section: The Roles Of Exs In Cns Injury Diseasesmentioning
confidence: 99%